A guerra como instrumento do poder presidencial nos EUA: o caso da intervenção na Líbia - Júnior Damin, Cláudio (Meridiano 47 - Journal of Global Studies, 2017)
We analyze the decision of U.S. participation in military intervention in Libya (2011). The main objective is to position Barack Obama's decision to use the military as an exercise of war powers of the president as commander in chief and as a doer of the deliberations of international multilateral agencies.